Life skills training, hope, and health: An interventional study in the North West of Iran during the COVID-19 pandemic - Haniyeh Safaralizadeh; Taghi Azarsa; Esmayil Zeinali; Rahim Sharafkhani (Elsevier, 2022)
Objectives: Suburbanization is associated with an individual's health. This study aimed to investigate the effect of life skills training on the hope and health of women referred to comprehensive health service centers in the suburbs of Khoy city. Study design: quasi-experimental study (Pre-test/Post-test with a control group) Methods: in this study, out of 5 comprehensive health service centers, two centers were selected as intervention and comparison groups, and from each center, 37 women were randomly selected. At first, both groups completed the Goldberg general health questionnaire and the Miller hope questionnaire, and the intervention group was taught life skills. At the end of the training, both groups were re-evaluated. Descriptive statistics such as frequency distribution and dispersion indices were used in data analysis. Mann-Whitney and Wilcoxon Signed Ranks Tests were used in inferential statistics. Results: Group training in life skills did not significantly affect hope (P.value = 0.972) and various aspects of health (P.value = 0.421). Conclusions: It seems that only interventions such as life skills training will not improve suburban women's hope and health. Perhaps improving social infrastructure and comprehensive living conditions in suburban areas will promote hope and health.